Strategic Planning for Information Systems at CV. Fancy Using the Ward and Peppard Method - Nova Indrayana Yusman; Muhamad Furqon; Rasyaa Nabilah (CoreID Journal, 2026)
Food distributors serving large retail chains face a dilemma that is easy to overlook: the reporting standards and system integration requirements imposed by corporate clients are essentially the same whether the supplier is a large logistics company or a two-person warehouse operation. CV. Fancy, a registered food distributor (NIB 0702250134384) based in Bandung, West Java, occupies exactly this position. The company supplies Alfamidi retail outlets and PT. Primafood manufacturing under long-standing contracts, yet its day-to-day operations remain entirely dependent on spreadsheets and mobile messaging. This paper reports a strategic information systems (IS) planning study carried out at CV. Fancy using the Ward and Peppard framework, with the aim of producing a practical IS/IT roadmap for the period 2026 to 2030. Data were gathered through in-depth interviews and direct observation during the first quarter of 2026. The analysis drew on Porter's Value Chain, SWOT, PEST, Porter's Five Forces, and the McFarlan Strategic Grid. The principal finding is that Cloud Warehouse Management System (WMS) and Order Management System (OMS) warrant immediate investment, as both fall in the Key Operational quadrant of the McFarlan Grid and directly address the operational gaps most likely to put existing contracts at risk. API integration with Alfamidi is identified as the medium-term priority that will determine the company's ability to retain and grow its enterprise client base. The phased roadmap developed from these findings offers a financially realistic path to digital capability for small distributors whose IT budgets are modest but whose clients expect enterprise-level performance